Midkine: A Novel Biomarker to Predict Malignancy in Patients with Nodular Thyroid Disease. (30th June 2016) - Kuzu, Fatih; Arpaci, Dilek; Unal, Mustafa; Altas, Ayfer; Haytaoglu, Gürkan; Can, Murat; Barut, Figen; Kokturk, Furuzan; Ilikhan, Sevil Uygun; Bayraktaroglu, Taner
Abstract : Background . Midkine (MK), a new heparin-binding growth factor, plays important roles in a variety of biological phenomena such as carcinogenesis, inflammation, and angiogenesis. In this study, we aimed to evaluate serum midkine (SMK) and nodular midkine (NMK) levels in patients with thyroid nodules to predict malignancy and whether there was any association between. Methods . A total of 105 patients (74 women, 31 men) with thyroid nodules were enrolled. The levels of SMK and NMK were measured. Any possible correlation between SMK, NMK, and biochemical, cytopathological, or radiological variables was investigated. Results . Both SMK and NMK were found to be higher in hypoechoic nodules with an irregular border and without a halo (p < 0.05 ). Serum MK levels were significantly higher in nodules with microcalcifications than nodules with macrocalcification or without calcification (p = 0.001 ). SMK levels were found to be correlated with NMK levels (SMK 0.63 ng/ml versus 1.04 ng/mL and NMK 0.55 ng/mL versus 0.55 ng/mL, r 2 = 0.54, p < 0.001 ). Conclusion . Both SMK and NMK can predict tumorigenesis of highly malignant/suspicious thyroid cytopathology and also well correlated with sonographic features of thyroid nodules. We suggest that MK levels may serve as an alternative biomarker, in conjunction with the cytopathological results in preoperative assessment of thyroid nodules.